Evaluasi Pelaksanaan Program Pelayanan Kesehatan Peduli Remaja (PKPR) Di Puskesmas Rangkah - A'yun, Lu'lu' Qurrotu; Qomaruddin, Mochammad Bagus (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
The most common problems experienced by adolescents are reproductive health problems including unwanted pregnancy (KTD), abortion, sexually transmitted infections (STIs) including Human Immunodeficiency Virus (HIV), sexual violence, and the problem of limited access to health information and services about health reproduction. The Ministry of Health of the Republic of Indonesia has developed a youth health program in Indonesia through the Youth Care Health Service (PKPR) since 2003 in health care. The Youth Care Health Care Program (PKPR) in the city of Surabaya began in 2010 at the Rangkah health center, then in the following year it developed. The problem raised in this study is the low percentage of coverage of the implementation of the PKPR program in Rangkah. The approach that will be used in examining the program implementation is seen from the input, process, and output components by looking at the 2014 PKPR National Standards Guidelines.Objective: This study aims to analyze the implementation of PKPR (Youth Care Health Services) program at Rangkah health center using a system based approach national standard of PKPR.Methods: This research uses descriptive research with a qualitative approach. The informant source was chosen purposively purposely selected by the researcher for the subject based on several criteria by adjusting to the objectives.Results: The results showed that the implementation of the PKPR program at the Rangkah Health Center was still not nationally standard. In addition, training for health center PKPR officers is still not routine in the implementation of both at the Rangkah health center. The Rangkah health center has collaborated in the implementation of PKPR programs across sectors, across programs and with certain NGOsConclusion: The implementation of the Rangkah Puskesmas PKPR program is in accordance with the national standard guidelines set by the Ministry of Health